Seismic behavior of shallow foundations shaking table experiments vs numerical modeling. - Paolucci, Roberto
The capability of a simplified approach to model the behavior of shallow foundations during earthquakes is explored by numerical simulation of a series of shaking table tests performed at the Public Works Research Institute, Tsukuba, Japan. After a summary of the experimental work, the numerical model is introduced, where the whole soil foundation system is represented by a multi-degrees of freedom elasto-plastic macro-element, supporting a single degree of freedom superstructure. In spite of its simplicity and of the large intensity of the excitation involving a high degree of nonlinearity in the foundation response, the proposed approach is found to provide very satisfactory results in predicting the rocking behavior of the system and the seismic actions transmitted to the superstructure. The agreement is further improved by introducing a simple degradation rule of the foundation stiffness parameters, suitable to capture even some minor details of the observed rocking response. On the other hand, the performance of the model is not fully satisfactory in predicting vertical settlements.
Keywords: Shallow foundations; Dynamic soil structure interaction; Shaking table tests; Nonlinear macro-element.